Indications for an antidepressive effect of thymosin alpha-1 in a small open-label proof of concept study in common variable immune deficiency patients with depression - Daniël G. Aynekulu Mersha; Sarah E. Fromme; Frank van Boven; Gara Arteaga-Henríquez; Annemarie Wijkhuijs; Marianne van der Ent; Raf Berghmans; Bernard T. Baune; Hemmo A. Drexhage; Virgil Dalm (Brain, Behavior, & Immunity - Health)
Background: A considerable proportion (21%) of patients with common variable immunodeficiency (CVID) suffers from depression. These subjects are characterized by reduced naïve T cells and a premature T cell senescence similar to that of patients with major depressive disorder (MDD). It is known that T cells are essential for limbic system development/function. Treatment with thymosin α1 (Tα1) is capable to increase the thymus output of naïve T cells. Objective: To treat CVID patients with a comorbid depressive episode with Tα1 to increase naïve T cells and thereby improve mood. Design: A small open-label, proof of concept trial. Five depressed CVID patients (Hamilton Depression Rating Scale, HDRS >12) could be treated with Tα1 (8 weeks, 1.6 mg daily subcutaneously, 1st week, thereafter 1.6 mg twice weekly). At the start, at 8 weeks and 8 weeks after the last injection, the HDRS was recorded and blood samples drawn for measuring naïve and memory T cells, Th17 and Treg cells, hsCRP, IL-6 and IL-7. Outcomes were compared to those of a contrast group (42 MDD patients, same severity but treated as usual (TAU)). Results: In all 5 depressed CVID patients HDRS decreased during Tα1 treatment (with average 52%, TAU decreased scores with 36% in MDD patients). All 5 CVID patients showed an increase in naïve/memory CD4+ and CD8+ T cell ratios, and in 4 of the 5 patients with detectable IL-6 levels reductions were recorded. TAU did not show such immune improvements. In the 8-week wash-out, depression recurred in the 2 most severe patients, while continued to improve in the others. Immune effects were not sustained in the wash-out. Conclusion: This preliminary small study suggests thymus hormone treatment to have antidepressive and related immune correcting effects. Data urge for larger placebo-controlled trials.